Hubungan Riwayat Diare dengan Kejadian Wasted pada Balita Usia 24-59 Bulan di Kecamatan Siulak Mukai Kabupaten Kerinci - Saputra, Rama; Kasyani, Kasyani; Iswanto, Iswanto (3031-8572, 2024)
Malnutrition is a major health problem in children under five because it can inhibit the process of growth and development. Of the prevalence of totally wasted in the world, 69% is in Asia and 23% is in Africa. The results of the 2018 Riskesdas, the prevalence of malnutrition in children under five, especially wasted in Indonesia, 2018 reached 13.8%. Meanwhile, public health problems are considered serious if the prevalence of waste ranges from 10.0%- 14.0% and is considered critical if 15.0%. Thus, the problem of waste is still a serious public health problem in Indonesia. The prevalence of waste in Jambi Province reached 17.0% and diarrhea in children under five was 7.7%. This study aims to determine the relationship between a history of diarrhea and the incidence of waste in Toddlers aged 24-59 months in Siulak Mukai District, Kerinci Regency. This study is a quantitative study with a cross-sectional design. This research was conducted in Siulak Mukai Subdistrict, Kerinci Regency on 24-28 February 2022. The population and sample in this study were data on all children under five in the research of Kasyani et al (2020) with a total of 210 respondents. The sampling technique is purposive sampling. Based on this study, most of the toddlers aged 24-59 months in Siulak Mukai District, Kerinci Regency did not experience wasted events (94.3%) and did not have a history of diarrhea (82.9%). There was no relationship between a history of diarrhea and the incidence of waste in Toddlers aged 24-59 months in Siulak Mukai District, Kerinci Regency (p = 0.255). It is expected that mothers and fathers of toddlers can participate and play an active role in information dissemination activities carried out by health workers in Siulak Mukai District, Kerinci Regency about diarrhea and wasting.